Association of Age of Metabolic Syndrome Onset With Cardiovascular Diseases: The Kailuan Study - Zegui Huang; Xianxuan Wang; Xiong Ding; Zefeng Cai; Weijian Li; Zekai Chen; Wei Fang; Zhiwei Cai; Yulong Lan; Guanzhi Chen; Weiqiang Wu; Zhichao Chen; et al. (Frontiers in Endocrinology, 2022)
BackgroundMetabolic syndrome (MetS) is associated with an increased risk of incident cardiovascular diseases (CVD), but the association between the new-onset MetS at different ages and the CVD risk remain unclear.MethodsThis was a prospective study comprising a total of 72,986 participants without MetS and CVD who participated in the Kailuan study baseline survey (July 2006 to October 2007). All participants received the biennial follow-up visit until December 31, 2019. In addition, 26,411 patients with new-onset MetS were identified from follow-up, and one control participant was randomly selected for each of them as a match for age ( ± 1 year) and sex. In the end, a total of 25,125 case-control pairs were involved. Moreover, the Cox proportional hazard model was established to calculate the hazard ratios (HR) for incident CVD across the onset age groups.ResultsAccording to the median follow-up for 8.47 years, 2,319 cases of incident CVD occurred. As MetS onset age increased, CVD hazards gradually decreased after adjusting for potential confounders. Compared with non-MetS controls, the HR and the 95% confidence interval (CI) for CVD were 1.84 (1.31–2.57) in the MetS onset age <45 years group, 1.67 (1.42–1.95) for the 45–54 years group, 1.36 (1.18–1.58) for the 55–64 years group, and 1.28 (1.10–1.50) for the ≥65 years group, respectively (p for interaction = 0.03).ConclusionsThe relative risks of CVD differed across MetS onset age groups, and the associations was more intense in the MetS onset group at a younger age.